The Digital Economy in Southeast Asia : Strengthening the Foundations for Future Growth - World Bank (World Bank, Washington, DC, 2019)
The signs of digital technology adoption are evident across Southeast Asia. In big cities, the use of mobile phones for messaging and social media has become ubiquitous. Ride-sharing services and delivery riders using apps to obtain their next booking are changing the face of urban transport and other services. As consumers go online to purchase products, they are recasting the future of brick-and-mortar retail businesses. The impacts of the digital revolution are not limited to a few prominent social networking sites, online businesses, or mobile apps. Digital platforms – a combination of technical innovation, new business models, and value proposition – in the private and in some cases the public sector, offer a range of products and services via digital channels. The use of digital technology is transforming – indeed, disrupting – all sectors, notably services such as logistics and finance, but also industrial production and agriculture. These are all visible manifestations of a growing digital economy. Southeast Asia is primed to embrace this digital revolution. There is a high level of interest from governments, businesses, and individuals in the region to support the growth of the digital economy and maximize its benefits. There is significant excitement about the rise of e-commerce platforms and app-based companies – including the region's own "unicorn" technology companies. Southeast Asia leads the world in some indicators on the use of the Internet, for example in social media and messaging.